The Effect of Music on Balance Parameters - Unver, Fatma; Buke, Meryem (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2023)
Objectives This study aimed to determine the effect of music on balance parameters in healthy individuals.Methods Forty-two participants were included in the study, mean age=23.3 (SD=5.31). Prokin Tecnobody balance device was used for balance measurements. Static and dynamic balance measurements on the dominant foot and bipedal stance were recorded while listening to high-intensity music and without music.Results In the study, there was a statistically significant difference in the dominant foot static mediolateral balance in measurements taken with music (p=0.013). But, there was no difference in other parameters (p>0.05). When examined by gender, it was found that the mediolateral balance scores of females on static and dynamic dominant feet were significantly higher in high-intensity music than males (p<0.05).Conclusion In healthy participants, music improves the mediolateral balance on the dominant foot. Therefore, high-intensity music can be a safe and motivating method to be used in addition to clinical applications.
Keywords: balance; music; healthy participant